2020
DOI: 10.1016/j.matchemphys.2019.122268
|View full text |Cite
|
Sign up to set email alerts
|

Meta-halloysite to improve compactness in iron-rich laterite-based alkali activated materials

Abstract: � Calcined laterite at 600 � C was used to synthesize geopolymers cured at ambient temperature. � Incorporation of meta-halloysite into geopolymer matrix extended the amorphous phase. � Compressive strength of laterite-based geopolymer increased with meta-halloysite added. � Adding an optimum of meta-halloysite powder inhibited the efflorescence formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 45 publications
0
20
0
Order By: Relevance
“…2c), is shifted to low wavenumbers in the range of 993-975 cm −1 and 1003-979 cm −1 for GMHA and GMHR geopolymer series respectively. The shift of this characteristic broad band at low wavenumber confirmed the dissolution of the meta-halloysite and the formation of the geopolymer gel [23]. From literature, this band is often used to determine the degree of polycondensation [32,33].…”
Section: Phases Evolutionmentioning
confidence: 81%
See 1 more Smart Citation
“…2c), is shifted to low wavenumbers in the range of 993-975 cm −1 and 1003-979 cm −1 for GMHA and GMHR geopolymer series respectively. The shift of this characteristic broad band at low wavenumber confirmed the dissolution of the meta-halloysite and the formation of the geopolymer gel [23]. From literature, this band is often used to determine the degree of polycondensation [32,33].…”
Section: Phases Evolutionmentioning
confidence: 81%
“…On the contrary, kaolinite (Al 2 Si 2 O5(OH) 4 ) is a simple layer aluminosilicate consisting of alternate layers of silica and alumina in tetrahedral and octahedral coordination, respectively [22] and typically occurs in platy form. Thermal treatment of halloysite and kaolinite clays from 550 to 800 °C causes their dehydroxylation resulting respectively in meta-halloysite and meta-kaolinite formation, required for the geopolymer synthesis [5,23]. However, the additional water content to halloysite with respect to kaolinite allows earlier decomposition and dehydroxylation conducing to meta-halloysite at lower temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the efflorescence is not only an aesthetic problem ( Fig. 1), but it could also have an impact upon the mechanical properties of the material [14][15][16] as well as damaging the protective layer around the steel reinforcement [15,17].…”
Section: Introductionmentioning
confidence: 99%
“…The authors of paper [ 23 ] confirmed that the addition of iron strengthened the geopolymeric binder and caused a good cohesion between different particles, and also increased the number of pores. Kaze et al [ 24 ] showed that the Si/Al ratio also has a great influence on the properties of calcined iron-rich laterite-based geopolymers. Davidovits [ 25 ] focused in his research on iron-rich geopolymers, and, at the same time, broke the current trend of iron having a negative impact on the mechanical properties of materials.…”
Section: Introductionmentioning
confidence: 99%